Action popularis in the system of criminal procedure in Spain - Pérez-Cruz Martín, Agustín-J (2021)
The exercise of the popular prosecution has allowed criminal proceedings in the gal, filesa malesa y time-export, baltarsar garzón cases or against financial entities (Novacaixagalicia and Caja Madrid), in this case, accusations about the former presidents of Caja Madrid, Rodrigo Rato and Miguel Blesa, among others, for the allegedly fraudulent use made with the ‘black’ cards, or about the former president of the Generalitat Valenciana, Francisco Camps, in the so-called «case of suits», or, perhaps, without a doubt , the most mediatic, directed, among others, against D.ª Cristina de Borbón and Grecia (Nóos case), daughter of S. M. the King Emeritus of Spain and sister of the current Head of the Spanish State (H. M. King Felipe vi), and her husband, were able to reach their end, by means of a sentence, being able to impose in some of these cases, or at the conviction of the accused, or imposition of a more serious penalty than that which was the object of accusation by the Public Prosecutor’s Office in response to the sentence requested by the popular prosecution.